TRANSLATION ERRORS IN TRANSLATIONS OF FICTION TEXT OR TRANSMITTING TRACKERS - Lakhtionova, K. (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
Everything has been changing all the time in our world. It concerns language and literature as well. New traditions are being formed, and old ones die. Literary activity (creativity) could not avoid such changes: flexible natural form (shape) came instead of classical writing, instead of classical writing, great and sentimental, inherent to French literature.Bokacho`s Style and perfectionism in language mean following the rules of language standard, starting from XIII century and finishing XVIII.Padre Grande was criticized too for glorification of toskana literary language and humiliation of local dialects.Outstanding personality of Dzhuzeppe Parini appears in early period of defining his positions, ignoring linguistic polemics, avoiding different extremes and exaggerations.Parini demonstrates society in ironic style, old such as “batrachomyomachia” – ironic “Illiada”, Moskeida” – Orlando`s statements: epical forms reflect plebeian picture of the world.Irony – is a kind of obsolete society, which didn`t understand its decline. Obsolete does its best to pretend modern, the more proud is the style, the poorer it is. This is the essence of Parini`s conception incarnated in his literary work “Giorno”(Day) which is based on irony, deep and sad.There are no doubts, that after the research and discuss about Parini, after publications of the translation in Spanish, not only ceased, but gained great interest of literary researches. It is clear, that some mistakes in translations were done, but we are not judges. The most important is basic content which is presented in the introduction of A. Prieto.  Analyzing translator`s mistakes from Italian language of original text into Spanish we have to focus on key phrase of Maris Isabel Honsales-Fernandes, that Spanish has not a lot in common with Italian. It is evident especially in translation of lexical units, where the translator did mistakes, that demonstrates not appropriate level of Italian language knowledge. We can call this phenomena “amici falsi del traduttore”, ignorance of particular lexis and meaning that lexical unit can have in both languages. This ignorance led to to misunderstanding even to ugliness and curvature of original text.The translator Marselo Arroyita-Chauresi, who is a poet himself, is much more to be desired. He has tried to follow the text of original in some cases. But he was not successful in his attempts.You can just imagine Spanish translation to be translated into language of original even being of 200 years old, which we could receive. Not a proper level of the Italian language and misunderstanding of some words, which in Spanish and Italian sound the same way.Translator`s work – hard labour which needs flawless knowledge of the language of original not to loose while translating artistic value or even to deface author`s concept. It just verifies common known truth: not to ignore even the slightest peculiarities of the text of original.The translator has to know lexis and a grammar perfectly, be able to use translator`s transformations in order to avoid such phenomena as failed translation and misrepresentation of the content of the text, especially if it is a poetry._____________References• De Sanktis, Franchesko. Istorija ital'janskoj literatury, T. II. Moskva, izdatel'stvo «Progress», 1964, str. 476-482.• Ponomar'ov O.D. Kul'tura slova: movno-stilіstichnі poradi. Kiїv, Libіd', 2011, 272 s.• Sal'e T. E. Pogreshnosti perevoda kak provodnik jazykovoj interferencii. Chetvertye Fedorovskie chtenija. Universitetskoe perevodovedenie. Vypusk 4. Sankt-Peterburg, 2003.• Tomashevskij N.B. Tradicija i novizna. Moskva, «Hudozhestvennaja literatura», 1981, 285s.• Enciclopedi Zanichelli. Milano, a cura di Edigeo, 1997.• Enciclopedi Zanichelli. Milano, a cura di Edigeo, 1997.• Gonzalez Fernandez Ma Isabel. Anotaciones a una traducción de Il Giorno de Parini. niversidad de Santiago de compostela, 1977, pp. 159-171.• Maestros italianos, Selección, introducción, estudio y notas de Antonio Prieto. Traducción de Marcelo Arroita-Jáuregui. Barcelona, 1962, pp.1277-1389.• Verba. Armario Gallego de Filología. Vol.4. Universidad de Santiago de compostela, 1977, 369p.
Keywords: language of original, language of translation, classical writing, language and style, irony, translator`s analysis, conception, Parini